Effect of moisture level and bale size on alfalfa hay quality - A. Laytimi; C. Grimes; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1985)
Third cutting alfalfa was baled in large I-ton rectangular bales and in small conventional bales at three moisture levels, low (10%), medium (16%), and high (22%). During 120 days of storage under a roof, the high-moisture, large bales heated the most, reaching 128 ÌŠ F by 2 days post baling in a first peak and 133 ÌŠF in a second peak by the 11 th day. Moderate heating occurred in the high-moisture, small bales (l08° F) and medium-moisture, large bales(103 ÌŠF). Only the high-moisture, small and large bales had significant loss of dry matter during storage. Also, heating decreased the water soluble carbohydrate and increased the concentration of cell wall contents by the 120th day of storage. A three-period collection and digestion trial with lambs showed higher voluntary intakes of small-bale hays than of large-bale hays and higher intakes of high-moisture hays than of low-moisture hays. Also, the dry matter and crude protein digestibilities were lowest for the high-moisture, large bale hay. These data indicate that baling alfalfa hay in large bales at 22% moisture results in extensive heating, which negatively affects storage loss, nutrient content, and digestibility.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Moisture level; Bale size; Alfalfa hay; Dry matter; Intake